Genomic regions associated with flag leaf and panicle architecture in rice (Oryza sativa L.) - Singh, Gurjeet; Jyoti, Subroto Das; Uppalanchi, Priyanka; Chepuri, Rushika; Mondal, Sejuti; Harper, Chersty L.; Elumalai, Punniakotti; Mix, Ken; Wagner, Nicole; Sanchez, Darlene L.; Samonte, Stanley Omar PB; Talukder, Shyamal K. (BMC genomics, 2024)
Flag leaf (FL) and panicle architecture (PA) are critical for increasing rice grain yield as well as production. A genome-wide association study (GWAS) can better understand the genetic pathways behind complex traits like FL and PA. In this study, 208 diverse rice germplasms were grown in the field at the Texas A&M AgriLife Research Center at Beaumont, TX, during 2022 and 2023 following Augmented Randomized Complete Block Design. After heading, eight different flag leaf and panicle architecture (FLPA) related traits were measured. GWAS analyses were performed to identify potential genomic regions associated with FLPA traits. A total of 97 quantitative trait loci (QTLs) (48 in 2022 and 49 in 2023) were distributed across all 12 chromosomes. GWAS revealed four QTLs (qSBPP4-2, qFLW6-2, qGNPP9, and qGWPP2-3) with phenotypic variation ranging from 11.7 to 22.3%. Two genetic loci were identified as multi-trait QTLs, i.e., S04_32100268 (qFLL4-1 and qFLA4-1) and S04_11552936 (qFLW4 and qFLA4-2) during 2022 and 2023, respectively. Additionally, these loci were further utilized to analyze candidate genes, and 65 genes were predicted in the 100-kb genomic region upstream and downstream. In silico expression analysis revealed 15 genes were expressed during the reproductive stage. These genes were associated with protein kinase, heat shock transcription factor family, sugar transporter conserved site and transcription factor bHLH95- like basic helix-loop-helix domain protein, as well as those that regulate the FLPA-related traits. Os04g0631100 was identified as a potential candidate gene that is highly expressed during the endosperm development stage, and it is associated with an important sugar transporter protein that will be helpful in grain improvement. GWAS results revealed four major and two multi-trait QTLs. Expanding their candidate genes, and expression analysis provide the genetic information for molecular improvement of the FLPA-related trait in rice breeding programs.